A Spike Protein-Based Subunit SARS-CoV-2 Vaccine for Pets: Safety, Immunogenicity, and Protective Efficacy in Juvenile Cats - Tabynov, Kairat; Orynbassar, Madiana; Yelchibayeva, Leila; Turebekov, Nurkeldi; Yerubayev, Toktassyn; Matikhan, Nurali; Yespolov, Tlektes; Petrovsky, Nikolai; Tabynov, Kaissar (Frontiers in Veterinary Science, 2022)
Whereas multiple vaccine types have been developed to curb the spread of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) among humans, there are very few vaccines being developed for animals including pets. To combat the threat of human-to-animal, animal-to-animal and animal-to-human transmission and the generation of new virus variants, we developed a subunit SARS-CoV-2 vaccine which is based on recombinant spike protein extracellular domain expressed in insect cells then formulated with appropriate adjuvants. Sixteen 8-12-week-old outbred female and male kittens (n=4/group) were randomly assigned into four treatment groups: spike protein alone; spike plus ESSAI O/W 1849102 adjuvant; spike plus aluminum hydroxide adjuvant; and a PBS control. All animals were vaccinated intramuscularly twice 2 weeks apart, with 5 µg of spike protein in a volume of 0.5 mL. On days 0 and 28 serum samples were collected to evaluate anti-spike IgG, antibody inhibition of spike binding to angiotensin-converting enzyme 2 (ACE-2), and neutralizing antibodies against wild-type and delta variant viruses, and hematology studies. At day 28, all groups were challenged with SARS-CoV-2 wild-type virus 106 TCID50 intranasally. On day 31, tissue samples (lung, heart, and nasal turbinates) were collected for histology, viral RNA detection and virus titration. After two immunizations, both vaccines induced high titers of serum anti-spike IgG that inhibited spike ACE-2 binding and neutralized both wild-type and delta variant virus. Both adjuvanted vaccine formulations protected juvenile cats against virus shedding from the upper respiratory tract and viral replication in the lower respiratory tract and hearts. These promising data warrant ongoing evaluation of the vaccine’s ability to protect cats against SARS-CoV-2 infection and in particular to prevent transmission.